ІМПЕРСЬКА АСИМІЛЯЦІЯ І НАЦІОНАЛЬНА ТРАДИЦІЯ В ПРАВОСЛАВНОМУ СЕРЕДОВИЩІ УКРАЇНИ ХІХ ñ початку ХХ ст. (Zaporizhzhia Historical Review, 2021)
Author analyses the nature and results of the national-political pressure of the Russian imperial structure on the orthodox environment in Ukraine in the XIX ñ the first half of the XX century. They are defined as the dependent from the power and duration of the Russian national domination, the peculiarities of the modernization of the empire and the spreading of the new social movements. The special attention is paid to the factor of the preservation of the national traditions and to the process of the Ukrainian rebirth, which become more and more powerful.